Regulation of microbial community structure, function, and nutrient of apple orchard soil by interplanting red clover - Jiao, Kuibao; Wu, Yuqi; Guo, Baitao; Zhang, Lei; Li, Yuze; Song, Penghui (Frontiers in Sustainable Food Systems, 2023)
Soil microbial communities are seen to be critical to the maintenance of soil health and quality. Many studies have suggested that soil microbial community composition is affected by different plant species. Based on this theory, we tried to improve the apple orchard soil microorganisms and nutrients by interplanting leguminous forage red clover (RC), meanwhile taking the natural mixed herb (NMH) naturally growing in the orchard as a control. The metagenomic analysis showed that interplanting red clover in the apple orchard markedly improved the soil microbial community composition, especially compared with natural mixed herbs, the abundance of Nitrospirae and Glomeromycota was higher. Compared with genus level, there are more unique bacteria species in RC, 84 species were unique to treatment (RC) soil and 43 species were unique to control group (NMH). The activities of glycoside hydrolase and carbohydrate-binding modules in RC were significantly higher than those in NMH, while compared with the control group (NMH), the activity of glycoside hydrolase and carbohydrate binding module in the treatment group (RC) was significantly higher, but the activity of glycosyl transferase was lower. In addition, only 5 of the 15 virulence factors they contain were lower in the RC, while the rest were higher in the control group. Based on the above results, we speculate that intercropping red clover can not only significantly improve soil quality, soil microbial community composition and soil fertility, but also effectively improve land use efficiency and reduce the use of chemical fertilizers.